Global economy and its influence on national industry: A case study of Malaysia - Rosnan, H.; Ismail, M.N. (2010)
The current scenario of global economies shows the changing trend in global economic activities. New industries like services industries are gaining their importance. This scenario has been made possible by the phenomena of globalisation. The forces brought about by globalisation phenomena pose many challenges and opportunities to national economies. Globalisation has significantly affects many countries, industries, businesses and citizens in many different ways. Hence, the present study is to investigate how national economy is affected by global economy by selecting Malaysian film industry as a case study. Subsequently, it examines the role of national government in ensuring harmonised national economic activities. Many developing countries acknowledge the necessity of government intervention to protect as well as promote the development of local industry. The findings are based upon interviews conducted with film industry players and relevant government agencies in Malaysia. This study suggests that the globalisation of film business provides opportunity for national film industry to penetrate global market and at the same time it posed threats especially in terms of competition from global players. The study suggests that government’s role is instrumental in ensuring the development of local industry. However, government intervention in the economies has led to the inefficiency in resources allocation. This study is perhaps one of the first to address the issue of government intervention in the film industry. Practically, it enhances the understanding on how global economies challenges local industry.